Revisiting the taxonomy of Pseudotiphia villosa (Fabricius, 1793) and notes on another Pseudotiphia Ashmead, 1903 species (Hymenoptera: Tiphiidae: Tiphiinae) - Bartalucci, M. Boni (Zootaxa, 2024)
The splitting between Pseudotiphia villosa (Fabricius, 1793) and Pseudotiphia olcesei (Tournier, 1889) is examined with the resulting restoration of the latter as a good species. The synonymy of Tiphia beckeri Tournier, 1889 with Tiphia villosa is proposed together with the new combination of the name Tiphia arenicola Kohl, 1889 under Pseudotiphia and its synonymy with Pseudotiphia caspica Boni Bartalucci, 2010.